Gender-affirming hormone therapy associated with multiple meningiomas and atypical histology in a transgender woman - Millward, Christopher Paul (BMJ Case Rep, 2021)
We present a 69-year-old transgender woman who underwent gender-affirming surgery in 1998 and gender-affirming hormone therapy (cyproterone acetate (CPA) and estradiol) since this time. Following an MRI scan to investigate tremor in 2013, an incidental left anterior clinoid and right petrous meningioma were identified. Subtotal surgical resection was achieved for the anterior clinoid meningioma (WHO grade 1, meningothelial subtype). At follow-up in 2016, an olfactory groove meningioma and left greater wing of sphenoid meningioma were identified. By 2017, both tumours, along with the petrous meningioma, demonstrated significant growth. In 2018, clinical decline was evident and MRI demonstrated further tumour growth. Surgery was scheduled and the olfactory groove meningioma was completely resected (WHO grade 2, chordoid subtype). Hormones were stopped, after which regression of the petrous meningioma was observed. This case demonstrates an association between high-dose CPA and estradiol and the development, growth and regression of meningiomas in a transgender woman.